Podróż do granic aktorstwa w teatrze Krystiana Lupy - Monika Żółkoś (Przestrzenie Teorii)
The article deals with the description of originality and uniqueness of acting in Krystian Lupa's performances. Author describes the process of creating the fictional characters in his art as psychical work, which is based on privacy of an actor. Trying to criticize the stereotypes about Lupa's performances, the author makes comparison with Tadeusz Kantor's theatre and his approach to the actors.